(untitled) (Rudarsko-geološko-naftni zbornik, 2022)
Iron-bearing minerals are the most important interfering compounds that found with bauxite reserves. Iron element has adverse effects on bauxite applications, including the use of bauxite in refractory soils. The purpose of this research is to investigate the possibility of iron removal from low-grade bauxite ores to utilize them in refractory industries. For achieving this purpose, iron removal tests were performed on bauxite samples with alumina to silica modulus of 0.73. After determining the appropriate iron removal method among the magnetic separation, calcination, and leaching (with H2SO4 and HCl) processes, optimal separation conditions were determined by tests were designed using the Taguchi method. According to leaching results using HCl for raw feed (un-calcined) provided the best result in iron removal. During this test Fe2O3 grade has decreased from 5.14 % to 0.08 % and, the alumina to silica modulus has increased to 0.75. Calcination of the concentrate obtained from this test has led to favorable results in reducing the Fe2O3 grade (0.04 %) and increasing the Al2O3 grade. Afterward, in tests designed by the Taguchi method, the effect of parameters such as time, process temperature, HCl concentration, and feed grain size on iron removal from bauxite by HCl leaching processes are discussed. According to the results, the best efficiency of iron removal for a feed grain size of 250 µm is achieved in the following conditions; 30 % HCl, process temperature of 25 ℃, and time of process 120 minutes. In this case, iron removal efficiency and Fe2O3 grade in process concentrate are 92.78 % and 0.56 %, respectively.